2006
DOI: 10.1370/afm.426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Improved Primary Care Access on Quality of Depression Care

Abstract: PURPOSE We wanted to determine whether a major improvement in access to primary care during 2000 was associated with changes in the quality of care for patients with depression.METHODS Health plan administrative data were analyzed by multilevel regression to compare the quality of care received by patients with depression between 1999 and 2001, a time without major changes in depression care guidelines. Approximately 6,000 patients with depression who received all care in a large multispecialty medical group d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…21,22 Many patients with chronic and complex problems, however, would rather see their trusted doctor than be seen quickly by any doctor, 23 and for such patients, advanced access may improve quality of care only if personal continuity is enhanced. 24 The average duration of the clinical encounter in the present study is similar to that previously reported in Glasgow 16 and the United Kingdom. 11 The shorter encounters in the most deprived areas are also in line with previous work.…”
Section: Mean Stresssupporting
confidence: 88%
“…21,22 Many patients with chronic and complex problems, however, would rather see their trusted doctor than be seen quickly by any doctor, 23 and for such patients, advanced access may improve quality of care only if personal continuity is enhanced. 24 The average duration of the clinical encounter in the present study is similar to that previously reported in Glasgow 16 and the United Kingdom. 11 The shorter encounters in the most deprived areas are also in line with previous work.…”
Section: Mean Stresssupporting
confidence: 88%
“…Moreover, our findings suggest that youths require a minimum of five outpatient visits for optimal contact. These findings are consistent with previous research showing the association between continuity of care and positive outcomes (e.g., reduced emergency room visits and hospitalizations, better medication adherence) (Cabana & Jee, 2004;Solberg et al, 2006). …”
Section: Discussionsupporting
confidence: 92%
“…16,[18][19][20][21][22] Fortunately, that study was supplemented by studying the approach to change by a small and exemplary family practice group. 21 Some of my previous experiences that are especially worth highlighting follow.…”
Section: Experiencementioning
confidence: 99%